Pengelolahan Sampah Rumah Tangga Menuju Lingkungan Berkelanjutan Melalui Produksi Pupuk Eco Enzyme Di Desa Nogo Rejo, Kecamatan Galang Kabupaten Deli Serdang - Nasution, Ade Nayla; Amidar, Suci Wulandari; Sinaga, Siti Aisyah; Ramadhani, Ira; Pulungan, Nur Aisyah; Harahap, Sri Rahma Yani (Bakti Sekawan : Jurnal Pengabdian Masyarakat, 2026)
Household waste consists of various types, one of which is organic waste that easily decomposes, such as vegetable residues, fruits, and kitchen waste. If not properly managed, organic waste can cause unpleasant odors, environmental pollution, and gas emissions that negatively affect the atmosphere. The problem faced by community partners is the limited knowledge and skills in sorting and managing organic waste, resulting in suboptimal utilization of organic waste. To address this issue, a community service activity was conducted to improve residents’ knowledge and skills in processing organic waste into value-added products. The activity applied a Participatory Action Research (PAR) approach by providing education on waste classification, explaining the benefits of environmentally friendly fermented liquid (eco enzyme), and conducting hands-on practice of the production process. The materials used included fruit peels, vegetable residues, brown sugar, and water fermented for approximately three months. Before the activity, most residents were unfamiliar with eco enzyme and productive organic waste management. After the activity, the results showed an improvement in residents’ understanding, as well as increased interest in utilizing the fermented liquid as liquid fertilizer, natural cleaner, and potential business opportunity. This program is expected to become a concrete step toward sustainable, environmentally friendly, and community-based waste management with economic value.